2020
DOI: 10.1186/s12879-020-4939-6
|View full text |Cite
|
Sign up to set email alerts
|

High contribution and impact of resistant gram negative pathogens causing surgical site infections at a multi-hospital healthcare system in Saudi Arabia, 2007–2016

Abstract: Background: Despite being largely preventable, surgical site infections (SSIs) are still one of the most frequent healthcare-associated infections. The presence of resistant pathogens can further augment their clinical and economic impacts. The objective was to estimate the distribution and resistance in SSI pathogens in Saudi Arabia and to compare them to the US National Healthcare Safety Network (NHSN) hospitals. Methods: Targeted SSI surveillance was prospectively conducted on several surgical procedures do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 30 publications
5
36
2
1
Order By: Relevance
“…Our prevalence of Staphylococcus aureus was similar to the rate described in a previous report done in Riyadh (12.6% vs 13.9%) [ 6 ]. We report a lower rate of MRSA (15.9%) compared to two previous studies made in Riyadh (24.4% and 30.3%, respectively) [ 28 ] but similar to the rate reported before in another study in Riyadh (17.5%) [ 29 ]. We report a higher susceptibility of Enterococcus species to vancomycin (85.9% vs 79.7%) compared to one study in Riyadh [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our prevalence of Staphylococcus aureus was similar to the rate described in a previous report done in Riyadh (12.6% vs 13.9%) [ 6 ]. We report a lower rate of MRSA (15.9%) compared to two previous studies made in Riyadh (24.4% and 30.3%, respectively) [ 28 ] but similar to the rate reported before in another study in Riyadh (17.5%) [ 29 ]. We report a higher susceptibility of Enterococcus species to vancomycin (85.9% vs 79.7%) compared to one study in Riyadh [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
“…As expected, HAI events were more frequent in the ICUs (37.2%) compared with non-ICU locations [HAI events in wards and outpatients were 32.9% and 29.9%, respectively], a finding which was previously described in local studies [ 10 , 28 ] and may reflect the epicenter role of ICU in both infections and antimicrobial resistance. The predominant isolates to cause HAIs were gram-negative organisms (71.9% vs. 28.1%); this finding was similar with many Saudi studies made in different cities in Saudi Arabia including Riyadh [ 6 , 28 , 29 ], Makkah [ 30 , 31 ], Dhahran [ 32 ], Bisha [ 33 ], and Aljouf [ 10 ]; with the majority being Escherichia coli (38%) accounting approximately for 52.9% of the gram-negative bacterial growth in line with previous national studies [ 7 , 29 , 30 , 32 , 34 ]. The second predominant isolates of the gram-negative organisms were the Klebsiella species (15.1%), this finding was similar to the bacterial isolates prevalence studies from Dhahran [ 7 ], and Riyadh [ 6 ].…”
Section: Discussionsupporting
confidence: 76%
“…In-vitro antibiotic susceptibility testing revealed that the isolated bacteria reacted differently to different antibiotics. Enterobacteriaceae like E. coli and Klebsiella showed very high resistance to ampicillin (92.2% and 95.7%) and first-generation cephalosporins like cefazolin (82.4% and 93.6%) similar to findings of other studies [13,19,20]. They also showed high resistance to amoxycillin-clavulanic acid (38-43%), gentamicin (45-48%), tetracycline (46-51%), and co-trimoxazole (37-45%).…”
Section: Discussionsupporting
confidence: 82%
“…[12]. E. coli has been implicated as a major pathogen in abdominal surgeries [19,20], and the source can be both endogenous (patient's gut flora) or exogenous (unhygienic surroundings, poor personal hygiene, or post-procedural contamination) [12,21]. Source of non-fermenters like Acinetobacter and Pseudomonas is usually exogenous like hospital surroundings or contaminated devices or dressings [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation